Academic Stress Levels of Students in Project-Based Learning - Humaera, Ririn; Saputra, Nefri Anra; Masta, Putri Khairina (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the level of academic stress among new students in the Electronic Engineering Technology Study Program at Batam State Polytechnic in the project-based learning (PBL) process. Academic stress often arises due to complex learning demands and significant changes in the learning environment for new students. The research method used was a quantitative descriptive design, involving 37 first-year student respondents. Data were collected through a questionnaire covering 10 aspects of academic stress. The results showed that most students (78.4%) experienced moderate stress, while the rest (21.6%) experienced low stress. The main factors causing stress included social anxiety (78.4%), time constraints (75.7%), and high task loads (70.3%). Meanwhile, dependence on teamwork (24.3%) and an unsupportive learning environment (29.7%) were the factors that caused the lowest levels of stress. These findings indicate that implementing PBL should be balanced with emotional support, effective time management, and faculty guidance to help new students adapt well.